Hysteresis and the Welfare Effect of Corrective Policies: Theory and Evidence from an Energy-Saving Program - Costa, Francisco; Gerard, François (Journal of Political Economy, 2021)
This paper provides stark evidence of hysteresis—the failure of an effect to reverse itself as its underlying cause is reversed—in energy demand. We estimate that half of the 23% reduction in residential electricity use caused by a 9-month-long policy that was imposed on millions of Brazilians has persisted for at least 12 years. We examine the implications of our finding by extending the traditional welfare analysis of corrective policies to allow for hysteresis. Our estimate highlights that failing to take hysteresis into account could severely bias the welfare evaluation of policies aimed at reducing (long-run) energy demand.